Theoretical studies on 3-bromo-2-methoxybenzonitrile using density functional theory. (2021) - Sugirtha Suni, N.Y.; Guru Prasad, L.; Brintha Malar, C.; Praveenkumar, Arockiasamy Ajay; Ganapathi Raman, R.
Abstract: Optimized molecular geometry, occupied maximum molecular orbital energy, mulliken atomic charges, unoccupied lowest molecular orbital energy, molecular electrostatic potential, dipole moment, first-order hyperpolarizability and polarizability of 3-bromo-2-methoxy benzonitrile is projected using 6–311++G(d, p) basis set of density functional theory (DFT) calculations. The spectrum of Fourier Transform Infrared (FTIR) as well as FT-Raman were explored and validated with the observed results. Hyperpolarizability of first order determined with the quantum chemical calculations illustrate the preferred compound as effective agent in the nonlinear optics for future applications. DFT was researching thermodynamic properties like enthalpy, entropy and Gibb's free energy.